INVASION OF Acacia decurrens Willd. AFTER ERUPTION OF MOUNT MERAPI, INDONESIA - Sunardi Sunardi; Sulistijorini Sulistijorini; Titiek Setyawati (SEAMEO BIOTROP, 2017)
The eruption of Mount Merapi in 2010 led to the dense establishment of Acacia decurrens Willd., an Invasive Alien Plant Species (IAPS). This dense cover occurred across all areas of Mount Merapi National Park (MMNP) in Java, Indonesia. This study aimed to describe the relationship between large-scale natural disturbance caused by volcanic eruption and the subsequent invasion of A. decurrens in MMNP. Vegetation data were collected using line transects at two locations: Cangkringan, which was affected by pyroclastic flow, and Selo, which was not affected. The distribution pattern and association of A. decurrens with other plant species at each site were analyzed using Non-Metric Multidimensional Scaling (NMDS). Microclimate variables, including temperature, humidity, light intensity, and soil moisture, were also recorded at each site. The correlation between species abundance and microclimate variables was further analyzed using Canonical Correspondence Analysis (CCA). The results showed that the population of A. decurrens was more dominant at the Cangkringan site compared to the Selo site. In Cangkringan, A. decurrens exhibited a clumped distribution pattern, whereas in Selo the species was distributed randomly. Ordination analysis (NMDS) indicated a positive association between A. decurrens and herbaceous plant species, while a negative association occurred between A. decurrens and other tree species. CCA analysis revealed that temperature and light intensity were positively correlated with A. decurrens abundance. Overall, the findings indicate that the invasion of this IAPS in MMNP is strongly associated with the disturbance caused by the 2010 Mount Merapi eruption.